Proximity to natural habitat enhances flower visitor diversity and pollination services in avocado orchards - Dymond, Keira; Celis-Diez, Juan L.; Díaz-Siefer, Pablo; Rojas-Bravo, Valeska; Martínez-Harms, Jaime; Potts, Simon G.; Garratt, Michael P. D. (Frontiers in Sustainable Food Systems, 2025)
Insect pollination is known to increase avocado yields, with wild pollinators likely playing an important role. In central Chile, the rapid expansion of avocado orchards has resulted in highly diverse natural habitats being replaced by plantations, potentially negatively impacting wild pollinators and thus avocado production. This study aimed to understand the role of natural habitats and wild pollinators in avocado production by (1) exploring the relationship between flower visitor abundance and diversity, and proximity to natural habitat, (2) quantifying the pollination effectiveness of different insect taxa, and (3) measuring the contribution to avocado production of insect pollinators and exploring how this varies with proximity to natural habitats. We conducted flower visitor observations and controlled pollination trials at different distances to natural habitat in three orchards in central Chile, across three years. The results showed that flower visitor abundance, visitation, richness, and diversity were significantly higher closer to natural habitats. However, this relationship varied across distances, with wild insect abundance and visitation rates approximately 2.55 times higher, richness around 1.6 times higher, and diversity 1.5 times higher at the natural habitat edge compared to further inside the orchard. Insect pollinators contributed significantly to avocado production, with almost no fruit set when pollinators were excluded. Hoverflies and other flies were identified as potentially important avocado pollinators. This study demonstrates the importance of natural habitats and wild insect pollination services in crop production. We recommend that growers implement land management practices that protect and restore natural areas in and around their orchards to support wild pollinators.